Consideraciones sobre la protección del derecho a la buena fama en Derecho canónico (Stato, Chiese e pluralismo confessionale, 2022)
SUMARIO: 1. Introducción - 2. Reflexiones acerca de la buena fama y el honor - 3. Desenvolvimiento histórico - 4. La buena fama en el Derecho canónico - 5. Reconocimiento jurídico - 6. Atentados contra la fama - 7. Murmuración, un arma que mata - 8. Murmuración. Delimitación conceptual - 9. Breve referencia histórica - 10. Pecado que atenta contra el prójimo - 11. Características y causas - 12. Regulación jurídica - 13. Los delitos canónicos de falsedad - 14. La reparación del daño - 15 Reparación y resarcimiento - 16. Restitución - 17. Satisfacción - 18. Indemnización - 19. Rescisión y restitución “in Integrum” - 20. Conclusión.Considerations on the protection of the right to good repute in canon law1ABSTRACT: Gossip is a sin that threatens the good reputation of neighbours. It belongs to the field of the so-called falsehood sins or crimes. They are clearly opposite to charity, whose transgression implies an attack against honour, the reputation of the accused and comunion in the Church, causing in turn a rupture in the order of social justice and the common good. It is a violation of the eight commandment of the Law of God which may be censored and combatted with firmness by the authority, does not admit ambiguity and must be undone in order to restore in their integrity the good reputation of the defamed.